Analysis of plant diversity legacy effects on conspecific and heterospecific plant-soil feedbacks - Wilschut, Rutger A.; van Kleunen, Mark (My University, 2025)
In this project, we established a greenhouse pot experiment with three phases, aimed at understanding the effects of plant diversity on the soil legacy effects established by single plants and their consequences for subsequent conspecific and heterospecific plant-soil feedbacks. In the first (pre-conditioning) phase, we established pots with plant communities of 1, 2, 4 or 8 plant species (out of a total pool of 8 plant species), with 40 pots for each diversity level, divided over five replicate blocks. This was set up in such a way that each block contained eight unique species monocultures, eight unique 2-species mixtures, eight unique 4-species mixtures and eight 8-species mixtures, in which all species occurred an even number of times. After 16 weeks of plant growth, aboveground biomass was collected, dried and weighed at the species level. The soil of each pot was collected for the second phase. To set up this phase, we mixed the soils from each diversity level separately for each of the five blocks. For example, soils from the eight unique monoculture pots present in each block were mixed. In this way we obtained replicate soil mixtures (five for each diversity level) that contained a legacy effect of all individual species, but that differed in at which surrounding plant diversity level these plant legacies were established. We then used these soil mixtures to set up the remainder of the experimental project, which from here can be seen as a classic plant-soil feedback experiment. In the second (conditioning) phase, we grew monocultures from each of the 8 species on each of the 20 soil mixtures (4 diversity levels*5 replicates). After 12 weeks, roots and shoots were harvested and dried. Then, soil from each of the 160 pots was divided over 8 small pots, which were planted with an individual of one of the 8 species to establish the feedback phase. This phase, with 1280 pots, lasted for 7.5 weeks, after which roots and shoots were harvested, dried and weighed. Description of individual files: "diversity_legacies_script.r": R-script associated to manuscript: "Community diversity shapes persisting soil legacies of individual plant species on subsequent plant performance". This script includes code to obtain all (supplementary) tables and figures associated with this manuscript.
"phase1_biomass_pot.txt" includes pot-level biomass data of plant communities (N = 160) with diversity levels 1,2,4 and 8 species, established in the abovementioned preconditioning phase. "phase1_biomass_species.txt" includes within-pot-level biomass data of single species growing at different pot-level diversities (1,2,4 and 8 species). "phase2_biomass.txt" includes species (N = 8) monoculture total biomass responses to soil mixtures of different diversity legacies established after the preconditioning phase. "phase3_biomass.txt" includes biomass responses of single plant species to conspecific and heterospecific monoculture soil conditioning of soils with different diversity legacies. "phase3_pairwisePSFs.txt" includes pairwise plant-soil feedback interaction outcomes (per diversity legacy level; calculated as done by Wandrag et al. 2020 New Phytologist) and pairwise phylogenetic distances, obtained from the phylogenetic tree used in van Kleunen et al. 2020 (Nature Communications).
Keywords: 570